The atlas of the Balkan linguistic area program - Adamou Evangelia; Sobolev Andrey N. (Balcanica)
This article presents the Atlas of the Balkan Linguistic Area (ABLA), a French- Russian research program that created an online database of language contact phenomena documented in the languages of the Balkans. This resource will be open access after its launch in 2025, enriching the fields of Balkan and areal linguistics. Specifically, ABLA consists of 93 phonological, morpho-syntactic, semantic, and lexical features. Each feature is matched to a map covering 60 localities across Balkan countries. Each map is accompanied by a chapter co-authored by the project contributors. The paper offers some preliminary results for the feature “Infinitive: Forms”. The online database in Wordpress is hosted by Huma-Num in France. ABLA, to be published by de Gruyter, is not only the first online database for the Balkans, an area shaped by multilingualism in forms that are rapidly disappearing, but also an example for other linguistic areas in the world